The kapwa-babae center enhancing women's well-being through a mixed-use women's center - Morales, Joanne Helena A. (College of Architecture, University of the Philippines Diliman, 2025)
Persons with disabilities, as the largest minority, face discrimination in their social, political, and personal lives. The Philippines has a total of 1,790,820 registered persons with disabilities under the Department of Social Welfare and Development. Only four out of the supposed nine mandated area vocational rehabilitation centers (AVRC) are in accordance with the Republic Act No. 2615, proving the lack of local prioritization of persons with disabilities. Quezon Province is no exception to this situation with 17,870 registered persons with disabilities. There are currently no active PWD rehabilitation facilities. All considering that it is important for persons with disabilities to develop physically, psychologically, and psychosocially, there is a lack of urgency for these developments. This study was able to successfully use landscape design and community-based rehabilitation (CBR) to develop a holistic rehabilitation facility for individuals with limited physical mobility to motivate local awareness and the production of rehabilitation facilities for persons with disabilities. The layers of the design follow the five elements of community-based rehabilitation: health, education, livelihood, social, and empowerment. These layers and functions were mirrored with the intention of building a holistic rehabilitation facility that can be localized and patterned into different regions. On-site visits, interviews, and community surveys were used to gather the necessary data for this research. This development contributes to promoting local and social awareness on the importance of providing Philippine PWD communities with a space where they can freely explore their independence in the built environment. Ultimately, this study outlines a landscape design framework for building a rehabilitation facility for persons with limited physical mobility using community-based rehabilitation.